2003
DOI: 10.1046/j.1523-1755.2003.00015.x
|View full text |Cite
|
Sign up to set email alerts
|

Maximal suppression of renin-angiotensin system in nonproliferative glomerulonephritis

Abstract: In nonnephrotic NPGN patients, standard doses of either ramipril or irbesartan lead to significant reduction of residual proteinuria and amelioration of the qualitative features suggestive of tubular damage. The enhancement of RAS suppression up to the maximal degree does not improve the antiproteinuric response and is coupled with a decrement of hemoglobin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 29 publications
1
27
1
Order By: Relevance
“…On the contrary, those using relatively high doses of ACEi and ARB failed to observe additive effects, such as observed in 5/6 nephrectomized rats and ADR-induced glomerulopathy [21, 34]. Similarly, in humans, combination of rather low doses of ACEi and ARB resulted in a more pronounced renoprotection than the use of either drug alone in non-diabetic proteinuric nephropathies [8, 9, 10], whereas the combined therapy did not improve the renal function than the use of ACEi or ARB alone of higher doses [6, 7]. In fact, another study also suggested that optimal antiproteinuric dose of either drug alone by dose-titration should be established before examining the effect of combination therapy of ACEi and ARB [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, those using relatively high doses of ACEi and ARB failed to observe additive effects, such as observed in 5/6 nephrectomized rats and ADR-induced glomerulopathy [21, 34]. Similarly, in humans, combination of rather low doses of ACEi and ARB resulted in a more pronounced renoprotection than the use of either drug alone in non-diabetic proteinuric nephropathies [8, 9, 10], whereas the combined therapy did not improve the renal function than the use of ACEi or ARB alone of higher doses [6, 7]. In fact, another study also suggested that optimal antiproteinuric dose of either drug alone by dose-titration should be established before examining the effect of combination therapy of ACEi and ARB [35].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the effectiveness of dual RAS blockade with both ACEi and ARB has not been established. Studies revealing a lack of any additive effects of the combination therapy in humans used the maximal or nearly maximal doses of either ACEi or ARB [6, 7], whereas others showing additive antiproteinuric effects used the combination of lower or halved doses of ACEi or ARB [8, 9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…Antiproteinuric and renoprotective effects of ACEI have been shown with four different ACEI (captopril, enalapril, benazepril, and ramipril) used in relatively low doses (78). High-dose ACEI therapy may be more antiproteinuric and more renoprotective than usual doses (4,72,79 -81), although mild anemia has been reported with ramipril at 20 mg daily (82). Current trends are to use the maximum recommended dose of ACEI, if tolerated (4,11,72,79 -81).…”
Section: Acei Therapy (Level 1)mentioning
confidence: 99%
“…Clinical and experimental studies have identified the reninangiotensin system as a key factor in development and progression of glomerular diseases (1)(2)(3). A chronically enhanced effect of the renin-angiotensin system is a central event in the development of proliferative and sclerosing changes in the glomeruli.…”
mentioning
confidence: 99%